Body composition of north and southbound migratory blackcaps is influenced by the lay‐of‐the‐land ahead. (25th February 2014) - Wojciechowski, Michał S.; Yosef, Reuven; Pinshow, Berry
<x xml:space="preserve">Abstract</x> The annual migration of small birds depends on the optimal management of time and energy. Since refueling at stopovers between flights consumes most of the birds' time and energy, selection of food‐rich sites, and timely departure therefrom are likely crucial to success. We examined this concept quantifying body composition of 200 migrating blackcaps, Sylvia atricapilla, in Eilat, Israel, using dual‐energy x‐ray absorptiometry and generated a model to predict body composition as it changes with body mass (mb). We then back‐calculated body composition of > 20 000 blackcaps ringed between 1984 and 2005, and tested the hypothesis that the amount of fuel that a bird stores determines the length of its stopover. We predicted that 1) if time‐constrained in spring, birds at the stopover site carry less than a maximum fuel load, but 2) if not time‐constrained, as in autumn, their fuel load is much higher than in spring. We found the change in body composition of blackcaps to be biphasic and correlated with increasing mb. At mb < ˜ 17.8 g, increasing mb is due to increasing lean mass (ml), while at mb > ˜ 17.8 g increasing mb results from increasing fat mass (mf), which is accompanied by decreasing ml. Body composition of blackcaps at a spring stopover site indicates that blackcaps leave stopovers as soon as they regain functionality of their digestive systems, but before laying down much mf. In autumn blackcaps arrive with fuel stores much larger than in spring. For these birds, the Eilat stopover apparently serves to complete fat accumulation before crossing the deserts ahead. We conclude that in spring, the decision to depart is not determined by the bird's fuel stores, especially when early arrival at the breeding site, and therefore time, is of the essence. In autumn, accumulating enough fuel to ensure successful crossing of the deserts ahead probably dictates stopover time.